2016
DOI: 10.7554/elife.15614
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic transcriptomes of 99 mouse strains reveal trans eQTL hotspots, splicing QTLs and novel non-coding genes

Abstract: Previous studies had shown that the integration of genome wide expression profiles, in metabolic tissues, with genetic and phenotypic variance, provided valuable insight into the underlying molecular mechanisms. We used RNA-Seq to characterize hypothalamic transcriptome in 99 inbred strains of mice from the Hybrid Mouse Diversity Panel (HMDP), a reference resource population for cardiovascular and metabolic traits. We report numerous novel transcripts supported by proteomic analyses, as well as novel non codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 71 publications
1
36
0
Order By: Relevance
“…Previous work from our lab and others have shown that gene-by-environment interactions can impact both gene expression and complex traits [23,24,25,26,27,28]. While splicing QTLs have been identified both in humans and mice [22,29,30,31], less is known about how gene-by-environment interactions may affect RNA processing. The first step to address this question is to characterize RNA processing in response to environmental perturbations.…”
Section: Introductionmentioning
confidence: 96%
“…Previous work from our lab and others have shown that gene-by-environment interactions can impact both gene expression and complex traits [23,24,25,26,27,28]. While splicing QTLs have been identified both in humans and mice [22,29,30,31], less is known about how gene-by-environment interactions may affect RNA processing. The first step to address this question is to characterize RNA processing in response to environmental perturbations.…”
Section: Introductionmentioning
confidence: 96%
“…We also identified 134 Supplemental Fig.S5; Supplemental Table S4). 135 Previous studies in model organisms have identified trans-eQTLs that regulate the expression of 136 many genes (Chesler et al 2005;Hasin-Brumshtein et al 2016;Albert and Kruglyak 2015); we refer to 137 these as 'master eQTLs'. We identified several master eQTLs, including one on chromosome 12 (70.19-138 Figure 4.…”
mentioning
confidence: 99%
“…Moreover, Dong et al (2009) [90] show that specific patterns of gene expression are associated with specific domains where distinct neural projection patterns emerge within the hippocampus, and Wolf et al (2011) [460] show that there is a strong predictive association of neural connections and gene expression within specific brain regions (also see [417]). Superimposed on this complexity are strain-dependent variations in the sexual dimorphism of certain brain nuclei [274, 366], and differences in how gene expression networks in the brain are modulated as a result of expression quantitative trait loci (eQTLs) that are sex-specific [293] (also see [151, 327]). Thus, it is important to consider just what we as scientists lose if we endeavor to extract molecular information from the brain without attempting to preserve the provenance of where the extraction took place.…”
Section: Why Does Location Matter?mentioning
confidence: 99%